2019
DOI: 10.1007/s11207-019-1513-8
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Two-Fluid Magnetohydrodynamic Model and Simulation of the Chromosphere

Abstract: The Sun's chromosphere is a highly dynamic, partially ionized region where spicules (hot jets of plasma) form. Here we present a two-fluid MHD model to study the chromosphere, which includes ion-neutral interaction and frictionalheating. Our simulation recovers a magnetic-canopy shape that forms quickly, but it is also quickly disrupted by the formation of a jet. Our simulation produces a shock self-consistently, where the jet is driven by the frictional-heating, which is much greater than the ohmic-heating. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Recently, Al Shidi et al. (2019) have shown that ion‐neutral frictional heating can be significant in the chromosphere, and lead to the generation of jets.…”
Section: Magnetohydrodynamic Waves In the Large‐scale Chromospherementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Al Shidi et al. (2019) have shown that ion‐neutral frictional heating can be significant in the chromosphere, and lead to the generation of jets.…”
Section: Magnetohydrodynamic Waves In the Large‐scale Chromospherementioning
confidence: 99%
“…Linear and nonlinear simulations of 10 mHz waves in an inclined rectangular packed ensemble of flux tubes with an internal/external field strength contrast of a few percent (Khomenko and Cally 2019) reveal that linear scattering greatly enhances the production of Alfvén waves compared to the horizontally uniform case; that nonlinear effects become important in the upper chromosphere; that the flux tube structuring enhances Poynting flux reaching the corona by about 35% and reduces reflection at the transition region by 50%; and that ambipolar diffusion, though notionally weak at this frequency, does have some effect in thermalizing a small fraction of fast waves in the chromosphere (see also Cally and Khomenko 2019) due to the steep gradients that develop there in the magnetically structured model, though this is not fully resolved numerically (10 km) and may in reality be stronger. Recently, Al Shidi et al (2019) have shown that ion-neutral frictional heating can be significant in the chromosphere, and lead to the generation of jets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of neutral atoms can be studied either in the framework of a single-fluid MHD model with Cowling conductivity or in the two-fluid MHD approach. In the two-fluid model ions+electrons and neutral atoms are treated as two separate fluids which are coupled by ion-neutral collisions (Zaqarashvili et al 2011a;Soler et al 2013;Leake & Linton 2013;Oliver et al 2016;Kuźma et al 2017;Al Shidi et al 2019;Wójcik et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(e.g., Cargill and Klimchuk 2004;Winebarger et al 2013;Klimchuk 2015;Xue et al 2016;Srivastava et al 2019). Apart from the magnetic reconnection generated heating, when we consider the two-or multi-fluid scales and relevant physical scenario especially in the context of the solar chromosphere, regardless of the waves the frictional heating can be significant as it simply accounts for the case where the ions are moving relatively to the neutrals and the friction between them can be significant (e.g., Al Shidi et al 2019). The similar physical scenario is true for the waves and instabilities also in the frame-work of the solar chromosphere where the deviation from MHD scales to fluid scales lead the additional physics (e.g., ion-neutral collisions; ambipolar diffusion, etc) leading the evolution and dissipation of the perturbations at much smaller spatial scales (e.g., Soler et al 2012;Díaz et al 2012;Soler et al 2013;Zaqarashvili et al 2013;Khomenko et al 2014a;Soler et al 2015a,b;Khomenko and Collados 2012;Martínez-Gómez et al2018).…”
Section: Introductionmentioning
confidence: 99%